2022
DOI: 10.1152/ajpheart.00300.2022
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between age, sex, and cerebrovascular reactivity to hypercapnia using traditional and kinetic-based analyses in healthy adults

Abstract: The effect of age and sex on intracranial and extracranial cerebrovascular function is poorly understood. We investigated the relationships between age, sex and cerebrovascular reactivity (CVR) to hypercapnia in 73 healthy adults (18-80 years, N=39 female). CVR to hypercapnia was assessed in the middle cerebral artery (MCA) using transcranial Doppler ultrasound and at the internal carotid artery (ICA) using duplex ultrasound. MCA CVR was characterised by peak MCA velocity (MCAv) response per mmHg increase in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 88 publications
0
16
0
Order By: Relevance
“…Impaired CVR to hypercapnia has been accepted as an indicator of the risk of cerebrovascular disease ( Juttukonda and Donahue, 2019 ). Clinical studies addressing the impact of age on CVR demonstrated lower hypercapnic vasodilation of healthy aging compared to young individuals, by using transcranial Doppler ultrasound or MRI ( Lu et al, 2011 ; Flück et al, 2014 ; Miller et al, 2019 ; Koep et al, 2022 ; Yew et al, 2022 ). Others reported preserved CVR in aging adults ( Kastrup et al, 1998 ; Galvin et al, 2010 ; Stefanidis et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired CVR to hypercapnia has been accepted as an indicator of the risk of cerebrovascular disease ( Juttukonda and Donahue, 2019 ). Clinical studies addressing the impact of age on CVR demonstrated lower hypercapnic vasodilation of healthy aging compared to young individuals, by using transcranial Doppler ultrasound or MRI ( Lu et al, 2011 ; Flück et al, 2014 ; Miller et al, 2019 ; Koep et al, 2022 ; Yew et al, 2022 ). Others reported preserved CVR in aging adults ( Kastrup et al, 1998 ; Galvin et al, 2010 ; Stefanidis et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, reduced CVR corresponded with the severity of cerebral ischemia ( Dettmers et al, 1993 ) and the risk for a future stroke attack ( Reinhard et al, 2014 ; Papassin et al, 2021 ). Accumulating experimental ( Mitschelen et al, 2009 ; Balbi et al, 2015 ) and clinical studies ( Lu et al, 2011 ; Flück et al, 2014 ; Miller et al, 2019 ; Koep et al, 2022 ; Yew et al, 2022 ) also testify a link between CVR decline and healthy aging. In addition to revealing compromised cerebrovascular health, CVR deficit appears to correlate with weakening cognitive function in aging, carotid stenosis and dementia ( Silvestrini et al, 2006 ; Mitschelen et al, 2009 ; Silvestrini et al, 2009 ; Lattanzi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 97%
“…Participants were recruited into age groups for young (18–35 years), middle aged (36–64 years) or older aged (65–85 years) adults, as done previously. 33 Exclusion criteria included diagnosed arterial hypertension, smoking, any known cardiometabolic or respiratory disease, the use of any prescribed medications known to influence cardiovascular function (e.g., statins, thyroid medication), a body mass index (BMI) >35 kg/m 2 and a resting systolic blood pressure (SBP) >139 mmHg or diastolic blood pressure (DBP) 89 mmHg. Participants were recruited based on biological sex assigned at birth.…”
Section: Methodsmentioning
confidence: 99%
“…4,31 Prior research has showed dynamic kinetic-based changes to CBF during a cerebrovascular challenge (carbon dioxide breathing) to be more sensitive compared to amplitude based measures to differences with advancing age. 32,33 Therefore, the inclusion of kinetic outcomes in addition to traditional amplitude-based inferences in the current study may offer additional insights into regulatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…9 Notably, neurovascular coupling (NVC), one of the main mechanisms affecting cerebral hemodynamics, is a phenomenon in which the body changes regional CBF according to neural activity and metabolism. 11 While the effects of sex on CBFV, cerebrovascular reactivity to carbon dioxide, and dCA of the MCA have been extensively reported, 12,13 less attention has been paid to the effect of sex on dCA of the posterior cerebral artery (PCA) in the supine position using transfer function analysis (TFA). The TFA utilizes a fast Fourier decomposition of stationary input and output signals to decompose them into the sum of sines and cosines of multiple frequencies.…”
Section: Introductionmentioning
confidence: 99%